Biomechanical comparison of all‐inside meniscal suture configurations for posterior root tear: Three conventional stitches versus delta‐grip stitch - Kyohei Ishibashi; Kyota Ishibashi; Takahiro Tsushima; Eiji Sasaki; Shohei Yamauchi; Yuka Kimura; Yasuyuki Ishibashi (Journal of Experimental Orthopaedics)
Abstract Purpose This study aimed to compare the biomechanical properties of four meniscal suture configurations—two simple sutures (TSS), two cinch sutures, a locking loop stitch (LLS), and a delta‐grip stitch (DGS)—for transtibial pullout repair of medial meniscus posterior root tears (MMPRTs) using porcine menisci. Methods Forty porcine menisci were randomly assigned to each suture configuration with all‐inside repair. All specimens were subjected to cyclic loading for 1000 cycles, followed by a load‐to‐failure test. We evaluated displacement after cyclic loading, the ultimate failure load and the mode of failure. Results No significant differences in displacement were observed between the configurations (p = 0.709). The DGS exhibited significantly higher ultimate failure loads (281.4 ± 53.5 N) compared to TSS (166.8 ± 84.5 N) and the LLS (119.7 ± 46.7 N) (p = 0.006 and p < 0.001, respectively). Suture breakage was observed in the DGS group, while meniscus cutout was observed in the other suture configuration models. Conclusion The results suggest that the DGS provides superior fixation strength and enhances MMPRT repair outcomes. Level of Evidence Level IV.